2016
DOI: 10.5195/ijms.2016.152
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Causal Link between Ankylosing Spondylitis and Inflammatory Bowel Disease: A Review of the Literature

Abstract: The link between ankylosing spondylitis and inflammatory bowel disease is unclear, however it is hypothesized that there is a causal link between the inheritance of a human leukocyte antigen B27 allele and the development of inflammatory bowel disease symptoms in ankylosing spondylitis patients. Research articles assessing the relationship between ankylosing spondylitis, inflammatory bowel disease and the human leukocyte antigen B27 antigen were collected from the PubMed database. Patients expressing the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…17 In addition, another study reported that the carriage of the HLA-B27 molecule was associated with the initiation of inflammation in articular and extra-articular sites of AS patients which agreed with the current study finding. 18 Moreover, Moshrif et al, 2018 found a similar positive rate of HLA-B27 carriage where 74.5% of their AS patients were HLA B27 positive. 19 On the other hand, there was no difference in HLA-B27 carriage between the patient and control groups (p > 0.05) in another previous similar study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…17 In addition, another study reported that the carriage of the HLA-B27 molecule was associated with the initiation of inflammation in articular and extra-articular sites of AS patients which agreed with the current study finding. 18 Moreover, Moshrif et al, 2018 found a similar positive rate of HLA-B27 carriage where 74.5% of their AS patients were HLA B27 positive. 19 On the other hand, there was no difference in HLA-B27 carriage between the patient and control groups (p > 0.05) in another previous similar study.…”
Section: Discussionmentioning
confidence: 94%
“…3 However, low fecal carriage of K. pneumoniae (12%) has been reported in spondyloarthritis patients in a different study. 18 This inconsistency might be attributed to differences in the collection and culture methods for fecal samples and the disease activity or stage at the time-point of sampling. 27 The current study demonstrated that AS patients had significantly higher levels of serum anti-Klebsiella pneumoniae IgG than controls.…”
Section: Discussionmentioning
confidence: 99%